Emergence of an Action Repository as Part of a Biologically Inspired Model of Speech Processing: The Role of Somatosensory Information in Learning Phonetic-Phonological Sound Features - Kröger, Bernd J.; Bafna, Tanya; Cao, Mengxue (Frontiers in Psychology, 2019)
A comprehensive model of speech processing and speech learning has been established. The model comprises a mental lexicon, an action repository and an articulatory-acoustic module for executing motor plans and generating auditory and somatosensory feedback information (Kröger & Cao, J Phonetics 53, 88-100). In this study a “model language” based on three auditory and motor realizations of 70 monosyllabic words has been trained in order to simulate early phases of speech acquisition (babbling and imitation). We were able to show that (i) the emergence of phonetic-phonological features results from an increasing degree of ordering of syllable representations within the action repository and that (ii) this ordering or arrangement of syllables is mainly shaped by auditory information. Somatosensory information helps to increase the speed of learning. Especially consonantal features like place of articulation are learned earlier if auditory information is accompanied by somatosensory information. It can be concluded that somatosensory information as it is generated already during the babbling and the imitation phase of speech acquisition is very helpful especially for learning features like place of articulation. After learning is completed acoustic information together with semantic information is sufficient for determining the phonetic-phonological information from the speech signal. Moreover it is possible to learn phonetic-phonological features like place of articulation from auditory and semantic information only but not as fast as when somatosensory information is also available during the early stages of learning.